PHYTOSTEROL CONTENT IN BENGKOANG (Pachyrhizus erosus) - Endang Lukitaningsih (Universitas Muhammadiyah Surakarta, 2012)
Bengkoang has long been used by ancestors as a raw material for cosmetics. In Indonesia, it is usually eaten raw, sometimes with salt, lemon juice and powdered chili. However, scientific evidences that support the use of bengkoang have not been widely published. Phytosterols from the bengkoang root have been isolated and identified based on their NMR spectrum data and mass spectrum. The result of the structure elucidation informed that ß-sitosterol and stigmasterol are major components of phytosterol in bengkoang root. Phytosterol content was about 0.02% of dry weight bengkoang or 2.76 % in petroleum ether extract of bengkoang, with a ratio of ß-sitosterol and stigmasterol (65:35). Therefore, bengkoang can be further exploited as a raw material of phytosterol supplement.